Addition of dexmedetomidine to bupivacaine in ultrasonography-guided paravertebral blockade potentiates postoperative pain relief among patients undergoing thoracotomy - Biçer,Cihangir (2019)
Abstract Background and objective: Thoracic paravertebral blockade is an alternative regional technique for comforting post-thoracotomy pain, thereby decreasing opioid consumption, postoperative nausea and vomiting, dizziness, respiratory depression and health care costs. The objective of this study was to investigate the effects of bupivacaine and bupivacaine plus dexmedetomidine on postoperative pain score and analgesic consumption in thoracotomy patients who had undergone ultrasonography-guided paravertebral blockade. Material and method: 93 ASA I-II patients aged 18-65 years were included in the study and scheduled for thoracic surgery. Prior to anesthesia induction, the paravertebral blockade procedure was performed by an anesthetist with ultrasonography. Cases were randomly stratified into three groups. The paravertebral blockade procedure was performed with 20 mL 0.5% bupivacaine injection in Group B (n = 31) and 20 mL 0.5% bupivacaine + 1 mL dexmedetomidine (100 µg) injection in Group BD. Group C received postoperative i.v. morphine via patient-controlled analgesia without paravertebral blockade. Post-operative pain scores were recorded in the recovery room and post-operatively using a VAS. Hemodynamic parameters, adverse effects and morphine consumption were also recorded. Results: No significant difference was determined between Group B and Group C regarding intra-operative adverse effects such as bradicardia and hypotension, while these adverse effects were significantly higher in Group BD (p = 0.04). VAS scores with rest and upon movement were significantly lower in Group BD compared to Group C (p < 0.001). Total morphine consumption was significantly lower in both Group B and Group BD in comparison with Group C (p < 0.001). In Group BD, HR and MAP were lower, but this was not clinically significant (p < 0.05). Conclusion: The addition of dexmedetomidine to bupivacaine lowers postoperative pain scores and morphine consumption in thoracotomy patients who receive ultrasonography guided paravertebral blockade.